STRATEGI PENDIDIKAN POLITIK PEMILIH PEMULA (GENERASI Z) MENJELANG PEMILU TAHUN 2024 DI KABUPATEN KUBU RAYA - Syarifah Nurma Afhiani; Elyta Elyta; Eka Apriyani (Universitas Hamzanwadi, 2024)
This research aims to analyze strategies for optimizing the role of Generation Z beginner voters through political education ahead of the 2024 elections in Kubu Raya regency. The success of holding elections can be seen from the high level of participation of community groups. The lack of knowledge and awareness in understanding democracy and less than optimal political education for first-time voters can allegedly reduce the involvement of first-time voters in the 2024 elections, especially in regency generation Z and millennials dominate Kubu Raya's population, novice voter require special attention. This research uses descriptive research methods with a qualitative approach. The data in this research were obtained from interviews with sources from beginner voters in Kubu Raya Regency, observations, and literature studies. This research found seven particular political education strategies implemented by the General Election Commission facing the 2024 elections in the Regency Kubu Raya in carrying out voter education programs to increase community participation.